Optimization of Process Parameter in the development of Ecofriendly Brake-pad from Coconut Fruit Fiber (Coir L.) And Oyster Sea Shells (Magallana-Gigas L.) - Second Justice Eziwhuo; C. V. Ossia; M.M. Ojapah (JMES: The International Journal of Mechanical Engineering and Sciences, 2024)
Coconut Fruit fiber, CFF (Coir L.) and Oyster Sea Shells, OSS (Magallana-gigas L.) were gathered from the waste peel and suspended in sodium hydroxide (NaOH) solution for 12h to remove the unwanted remnant. The fibers were washed with water to remove the residual NaOH and sun-dried for 5 days. The dried CFF and OSS was grounded into powder-form using electric grounding machine. Thereafter sieved to 75, 125 and 175µm grain size. The based materials, CFF and OSS were prepared into organic-based brake pads by compressive molding with different formulations of base materials, epoxy resin, hardener, graphite friction modifiers and copper chips. A commercially brake pad were used as control. The characterization of the brake pad produced are mostly influenced by molding pressure and grain sizes, respectively. Hence, the density, hardness, compressive strength, and tensile strength test values decreased with increase in grain size. Finally, the optimal values of all responses fall within standard requirements of brake pads as it compared favorably with commercially brake pads. Therefore, it can be concluded that the characterization of the developed brake pad compares satisfactorily and is capable of producing less vibration and noise during application of braking due to its high mechanical properties. Therefore, coconut fruit fibers and oyster sea shells can serve as a possible replacement for asbestos brake pad production.